Exploring antibiotic resistance mechanisms in Mycobacterium abscessus for enhanced therapeutic approaches - Nguyen, Thanh Quang; Heo, Bo Eun; Jeon, Seunghyeon; Ash, Anwesha; Lee, Heehyun; Moon, Cheol; Jang, Jichan (Frontiers in Microbiology, 2024)
Mycobacterium abscessus, a leading cause of severe lung infections in immunocompromised individuals, poses significant challenges for current therapeutic strategies due to resistance mechanisms. Therefore, understanding the intrinsic and acquired antibiotic resistance of M. abscessus is crucial for effective treatment. This review highlights the mechanisms employed by M. abscessus to sustain antibiotic resistance, encompassing not only conventional drugs but also newly discovered drug candidates. This comprehensive analysis aims to identify novel entities capable of overcoming the notorious resistance exhibited by M. abscessus, providing insights for the development of more effective therapeutic interventions.